2004
DOI: 10.1016/j.ejpain.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, co‐morbidity, and impact on health‐related quality of life of self‐reported headache and musculoskeletal pain—a gender perspective

Abstract: There are major differences between men and women in the prevalence and severity of self-reported pain in the population. Biological factors may explain some of the differences but the main explanation is presumably gender disparities in work, economy, daily living, social life and expectations between women and men. Although improved working conditions are of importance, deeper societal changes are needed to reduce the inequities in pain experiences between women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
223
6
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(272 citation statements)
references
References 48 publications
(74 reference statements)
33
223
6
10
Order By: Relevance
“…A high prevalence of these degenerative musculoskeletal diseases has been reported [23], and prevalence of concurrent upper and lower extremity pain in patients older than 65 years is reportedly greater than 40% [25]. Furthermore, musculoskeletal pain or disability is reportedly more prevalent [18] and more severe in women [8], which concurs with our findings. This sex effect was not confined to a specific physical subscale but rather involved all physical components of the SF-36, DASH, and WOMAC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A high prevalence of these degenerative musculoskeletal diseases has been reported [23], and prevalence of concurrent upper and lower extremity pain in patients older than 65 years is reportedly greater than 40% [25]. Furthermore, musculoskeletal pain or disability is reportedly more prevalent [18] and more severe in women [8], which concurs with our findings. This sex effect was not confined to a specific physical subscale but rather involved all physical components of the SF-36, DASH, and WOMAC.…”
Section: Discussionsupporting
confidence: 82%
“…Musculoskeletal disorders are among the most frequently occurring chronic conditions that affect the general population and have substantial impacts on physical activity, mental state, and quality of life (QOL) [8,16]. The prevalence of musculoskeletal disorders increases with age, and they are the leading cause of disability, especially among those older than 65 years [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…A 2002 cross-sectional survey of 4,506 Swedes found that SF-36 scores differed by gender. The authors hypothesize that these differences were due, in part, to gender disparities in work, income, daily living, social life, and expectations between men and women [49]. The authors of this study also noted that there were gender differences in the prevalence and severity of self-reported pain associated with headaches and musculoskeletal disorders, which has also been observed by others for rheumatoid arthritis [50], irritable bowel syndrome [51], fibromyalgia [52], and chronic fatigue syndrome [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Physician bias towards obese patients may contribute to the assumption that their painful musculoskeletal (MSK) symptoms are weight related. 3 However, the published literature does not support the association between weight and many MSK conditions.…”
Section: Introductionmentioning
confidence: 99%